374 Access to specialist care and injury survivability: a study of prehospital fatalities. (20th November 2022) - Davie, Gabrielle; Lilley, Rebbecca; Graaf, Brandon de; Ameratunga, Shanthi; Dicker, Bridget; Civil, Ian; Reid, Papaarangi; Branas, Charles; Kool, Bridget
Abstract : Background: Although reducing the time from injury to definitive care has been shown to achieve better outcomes for patients, the relationship between injury incident location and access to specialist care has been largely unexplored. Aims: To determine the number and distribution of prehospital trauma deaths in New Zealand (NZ) without timely access (>60 minutes) to a hospital with surgical and intensive care capabilities, overall and by estimated injury survivability. Methods: Prehospital injury deaths in 2009–2012 identified from NZ's Mortality Collection and Hospital Discharge data were linked to Coronial files to estimate, for the trauma subset, injury survivability. Using geographical locations of injury, time from Emergency Medical System call-out to arrival at the closest specialist hospital was estimated. Results: Of 1, 752 prehospital trauma fatalities, 14.7% (95%CI 13.0, 16.4) had potentially survivable injuries that occurred in locations without timely access. More than half of these died as a result of a motor vehicle traffic crash. Through using geospatial techniques, 'hot spot' locations of potentially survivable injuries without timely access to specialist major trauma hospitals were apparent. Conclusion: Approximately 15% of prehospital trauma fatalities in NZ that are potentially survivable occur in locations without timely access to advanced level hospital care. Continued emphasis is required on both improving timely access to advanced trauma care, and on primary prevention of serious injuries. Learning Outcomes: Decisions regarding trauma service delivery, a modifiable system-level factor, should consider the geographic distribution of locations, in particular clusters, of these injury events alongside the resident population distribution.